2021
DOI: 10.1001/jamadermatol.2021.3161
|View full text |Cite
|
Sign up to set email alerts
|

Patient Quality of Life After Interpolated Flap Repair of Nasal Mohs Surgery Defects

Abstract: IMPORTANCESingle-center studies have shown that patients report better skin cancer-specific quality of life (QOL) after Mohs micrographic surgery (MMS), but it is unclear whether this improved QOL applies to patients after MMS and complex reconstruction in cosmetically sensitive areas.OBJECTIVE To evaluate patient QOL after MMS and interpolation flap reconstruction for patients with nasal skin cancers. DESIGN, SETTING AND PARTICIPANTSThis multicenter prospective survey study used the Skin Cancer Index (SCI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…2 The information on scar erythema drawn from our study can help counsel patients, manage their expectations, and therefore improve QOL perioperatively. 2,13 In the future, there may be clinical utility and feasibility of computer-assisted image processing to quantify and track skin erythema over time in other dermatologic conditions, such as rosacea. 18 In addition, this technology may be used alongside tele-dermatology to quantitatively assess photos submitted by patients.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…2 The information on scar erythema drawn from our study can help counsel patients, manage their expectations, and therefore improve QOL perioperatively. 2,13 In the future, there may be clinical utility and feasibility of computer-assisted image processing to quantify and track skin erythema over time in other dermatologic conditions, such as rosacea. 18 In addition, this technology may be used alongside tele-dermatology to quantitatively assess photos submitted by patients.…”
Section: Discussionmentioning
confidence: 94%
“…1,13 Scar cosmesis contributes to QOL and has implications on mental health and function. 2 The information on scar erythema drawn from our study can help counsel patients, manage their expectations, and therefore improve QOL perioperatively. 2,13 In the future, there may be clinical utility and feasibility of computer-assisted image processing to quantify and track skin erythema over time in other dermatologic conditions, such as rosacea.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Retrospective evidence finds that the drop in quality of life improves significantly at 16 weeks postflap takedown with no lasting, long-term impact (p < 0.001). 72 Many reconstructive surgeons advocate for the use of Doppler signaling despite the reliable anatomical location of the supratrochlear artery. 73 However, Stigall et al have demonstrated no difference in complication rates or long-term outcomes when Doppler signaling was or was not used.…”
Section: Reconstruction Techniquesmentioning
confidence: 99%